Origin and challenges of aymara schools in the peruvian andean south of the twentieth century - Ruelas-Vargas, David (2021)
The article addresses the ontological understanding of Aymara indigenous education, historical facts and challenges to the political, economic and social system at the beginning of the 20th century, in the Peruvian Altiplano, Puno region. These schools originated clandestinely, due to the educational exclusion of the native Aymara population, generated by the governments of the day. For indigenous teachers, the only way to free themselves from oppression was with the creation of rural schools, which became instruments of liberation from the serfdom and semi-feudal system, established by the gamonales and oligarchic governments. The objective of the study is to identify the origin and challenges of Aymara schools in the Peruvian Andean south of the 20th century, and to contribute to the history of regional and national education, the applied research methodology was the descriptive historiographic approach, which were reviewed Primary and secondary documentary sources for the analysis and validation of the data, fundamentally. It is concluded that at the beginning of the 20th century Aymara schools originated as a result of the oppression, exploitation, usurpation of their lands by gamonalism and the oligarchy, education for the Aymara meant a way of liberation towards a just society. The result of the study made it possible to identify the origin of rural schools and the first Aymara indigenous teacher Manuel Zúñiga Camacho from southern Peru - Puno in 1902, as a pioneer of clandestine schools in the Puno Altiplano, the original population began to educate themselves to face the gamonal system.